High‐resolution, relational, resonance‐based, electroencephalic mirroring (HIRREM) improves symptoms and autonomic function for insomnia: A randomized, placebo‐controlled clinical trial. Issue 11 (17th September 2020) - Tegeler, Catherine L.; Shaltout, Hossam A.; Lee, Sung W.; Simpson, Sean L.; Gerdes, Lee; Tegeler, Charles H.
Abstract: Introduction: Effective insomnia interventions that also address autonomic dysregulation are lacking. We evaluate high‐resolution, relational, resonance‐based, electroencephalic mirroring (HIRREM ® ), in a randomized, controlled clinical trial. HIRREM is a noninvasive, closed‐loop, allostatic, acoustic stimulation neurotechnology, to support self‐optimization of brain rhythms. Methods: One hundred and seven adults (mean age 45.7, SD ± 5.6, 73 women), with Insomnia Severity Index (ISI) scores of ≥15, received ten, 90‐min sessions of HIRREM, with tones linked to brainwaves (LB, 56), or random tones not linked to brainwaves (NL, 51), as an active, sham placebo. Outcomes were obtained at enrollment (V1), 1–7 days (V2), 8–10 weeks (V3), and 16–18 weeks (V4) after intervention. Primary outcome was differential change in ISI from V1 to V3. Secondary measures assessed depression (BDI), anxiety (BAI), quality of life (EQ‐5D), and a sleep diary. Ten minute recordings of HR and BP allowed analysis of heart rate variability (HRV) and baroreflex sensitivity (BRS). Results: Of 107 randomized, 101 completed the intervention. Intention‐to‐treat analysis (107) of change from V1 to V3 revealed a mean reduction of ISI in NL of −4.93 ( SE ± 0.76) points, with additional, significant reduction of −2.05 points (0.74) in LB (total reduction of −6.98, p = .045). Additional reduction of −2.30 points (0.76) was still present in the LB at V4 ( p = .058). Total ISI reduction from V1 to V4 was −5.90 points for NL and −7.93 points in LB. There were group differences ( p < .05) for multiple HRV and BRS measures (rMSSD, SDNN, HF alpha, and Seq ALL), as well as total sleep time, sleep onset latency, and sleep efficiency. There were no serious adverse events. Conclusions: Results of this controlled clinical trial showed clinically relevant reduction of insomnia symptoms with HIRREM, over, and above an active, sham control, with associated, durable improvement in autonomic cardiovascular regulation. Abstract : This controlled clinical trial observed significant added benefit to reduce symptoms of insomnia with use of a closed‐loop, acoustic stimulation neurotechnology that echoes tones linked to brainwaves (HIRREM), compared to a sham using randomly generated tones. There was also significant improvement in multiple measures of autonomic cardiovascular regulation, with durability to 4 months postintervention, and group differences for sleep efficiency, total sleep time, and sleep onset latency. Results suggest that this noninvasive, nondrug intervention could provide a viable alternative for moderate to severe insomnia.